EFFECT OF DIFFERENT REGIME OF WATERING ON MILK YIELD AND MILK CONSTITUENTS IN LACTATING MURRAH BUFFALOES - Singh, akhilesh; Jain, Aklank; Lakhani, G.P (Indian Journal of Animal Production and Management, 2017)
Seventy to ninety percent of the total water consumed by the lactating cow is drinking water. Approximately 26 to 34 percent of total water intake is used in milk secretion. In India, generally watering of the animal is done after milking in the morning and before milking in the evening and rest of the time animal remains without drinking water which adversely affect in milk production. Therefore, present study was undertaken to find out the effect of different regime, of watering were studied on milk yield and milk constituents in lactating Murrah buffalos. The animals were subjected to four regime of watering, adlib (Group I), before milking (Group II), after milking (Group III) and before and after milking (Group IV). Results revealed that, the average daily milk yield was highest in group II (8.96 liter) and differed significantly (P<0.01) from group I, III and IV. The maximum and minimum milk fat percent was found in group III (8.48 Â± 0.12) and group I (7.44 Â± 0.14) respectively. Milk fat percent of group III was significantly differed from group I and group II. The solid not fat percent in the group III differed significantly (P<0.01) from I and II and group IV. The protein and lactose percent of milk among all the treatment group did not differed significantly, where as the mineral percent of the milk in group I significantly differed (P<0.05) from group II, III and IV. Therefore, it can be concluded that, watering of buffalo one hour after milking yielded more milk. The fat and SNF percent of the milk was higher when watering is done after the milking.